2014
DOI: 10.1097/gme.0b013e3182a433f7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies and epistasis analyses of candidate genes related to age at menarche and age at natural menopause in a Korean population

Abstract: Novel SNPs and synergistic interactions between candidate genes are significantly associated with age at menarche and age at natural menopause in a Korean population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Recent genome-wide association studies (GWASs) among women of European ancestry have identified at least 106 genetic loci for AM (He et al 2009;Ong et al 2009;Perry et al 2009;Sulem et al 2009;Elks et al 2010;Perry et al 2014) and 21 loci for ANM (He et al 2009;Stolk et al 2009;Stolk et al 2012). However, only 24 AM loci and 9 ANM loci have been replicated in women of either Asian or African ancestry and no novel loci have been identified in these non-European populations (Liu et al 2009;Chen et al 2012;Shen et al 2013;Spencer et al 2013;Tanikawa et al 2013;Delahanty et al 2013;Carty et al 2013;Demerath et al 2013;Pyun et al 2014;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome-wide association studies (GWASs) among women of European ancestry have identified at least 106 genetic loci for AM (He et al 2009;Ong et al 2009;Perry et al 2009;Sulem et al 2009;Elks et al 2010;Perry et al 2014) and 21 loci for ANM (He et al 2009;Stolk et al 2009;Stolk et al 2012). However, only 24 AM loci and 9 ANM loci have been replicated in women of either Asian or African ancestry and no novel loci have been identified in these non-European populations (Liu et al 2009;Chen et al 2012;Shen et al 2013;Spencer et al 2013;Tanikawa et al 2013;Delahanty et al 2013;Carty et al 2013;Demerath et al 2013;Pyun et al 2014;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…ADAMTS9 is one of these genes. The relationship between the ADAMTS9 and SMAD3 genes is associated with natural menopause age (40). Bone mineral densitometry (BMD), an examination method to determine osteoporosis, is influenced by several genetic and environmental factors.…”
Section: Menopause and Adamtsmentioning
confidence: 99%
“…Values with the same letters indicate that no significant differences were found between the groups. AST, aspartate aminotransferase; ALT, alanine aminotransferase; DBP, diastolic blood pressure; EMA, early menarche age; FBG, fasting blood glucose; Hb1Ac, glycated hemoglobin 1ac; HDL-C, high-density lipoprotein cholesterol; HOMA-IR, homeostatic model assessment for insulin resistance; LDL-C, low-density lipoprotein cholesterol; LMA, late menarche age; NMA, normal menarche age; SBP, systolic blood pressure; TC, total cholesterol; TG, triglycerides [34], which contributes to the development of diabetes [35]. During the preparation of this manuscript, two studies have just reported in Korea which found inverse association between early age at menarche and diabetes.…”
Section: Odds Ratios (Ors) For Diabetes By Age At Menarchementioning
confidence: 99%